2014
DOI: 10.1166/asfo.2014.1065
|View full text |Cite
|
Sign up to set email alerts
|

Colorimetric Assays for the Detection of Hg(II) Ions Using Functionalized Gold and Silver Nanoparticles

Abstract: In this work, we are reporting a simpler alternative method for field-portable, rapid, inexpensive and accurate optical detection of mercury in water. The sensing properties of the functionalized gold and silver nanoparticles have been utilised in this contribution. Functionalization of nanoparticles has been carried out by betacyanins molecules present in the aqueous extract of beet root (Beta vulgaris). The stability of the sol may be due to the formation of coating of betacyanins on the surface, which might… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The lowest concentration of mercury ions (Hg 2+ ) in water samples was detectable in the most recent study using anthocyanin hydrogel (LOD 0.2 µM by linear-graph estimation) [110], followed by curcumin-gold nanoparticles, with a visual LOD of 2 µM [86], compared to betalain (LOD 25 µM) and chlorophyll (LOD 2.7 µM with UV-Vis spectrophotometry, 60 µM visually) [71,117]. Mohan and Prakash also reported that a colour change at 10 µM can be visually observable, but the lowest concentration for naked eye observation was not reported [110].…”
Section: Comparative Results Of Metal Detector Using Natural Pigmentsmentioning
confidence: 99%
See 3 more Smart Citations
“…The lowest concentration of mercury ions (Hg 2+ ) in water samples was detectable in the most recent study using anthocyanin hydrogel (LOD 0.2 µM by linear-graph estimation) [110], followed by curcumin-gold nanoparticles, with a visual LOD of 2 µM [86], compared to betalain (LOD 25 µM) and chlorophyll (LOD 2.7 µM with UV-Vis spectrophotometry, 60 µM visually) [71,117]. Mohan and Prakash also reported that a colour change at 10 µM can be visually observable, but the lowest concentration for naked eye observation was not reported [110].…”
Section: Comparative Results Of Metal Detector Using Natural Pigmentsmentioning
confidence: 99%
“…Recent studies have reported that different types of metal detectors have been developed using red beet pigment (Table 1), namely a functionalised nanoparticles [71] and a smartphone-based analyser [58]. Formerly in 2013, Gonçalves et al used betanin (additive E-162) pigment as a colorimetric sensor for the detection of calcium dipicolinate (CaDPA) in bacterial spores [73].…”
Section: Betalainsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is to mention here that the concentration of Cu, Ni, Co and Zn solution below 200 µl/ml of AgNPs did not affect the absorbance SPR of AgNPs. Due to strong electron donating ability which is responsible for the complex formation of Cu, Cd, and other metals with silver, the instability in silver nanoparticles was profoundly noted as compared to Zn and Ni [28][29][30].…”
Section: Scanning Electron Microcopymentioning
confidence: 99%